(untitled) (Applied Biological Research, 2013)
Salicylic acid (SA) is a well known inducer of systemic acquired resistance (SAR) in several plants. In present study the ability of SA to induce resistance in Indian mustard (Brassica juncea) RLM619 was investigated. SA (10 and 50 ppm) treated seeds of B. juncea, germinated in petri-plates, showed maximum of 34.0, 21.7 and 28.5% increase in defense-related enzyme activities viz., peroxidase (PO), phenylalanine ammonia lyase (PAL) and superoxide dismutase (SOD) in hypocotyls, respectively, as compared to water-treated control. Similar trend was observed in cotyledonary leaves of germinated seedlings. Corresponding changes in phenolic contents was also observed. SA treatment @ 50 ppm showed maximum increase in defense enzymes and phenolics on all the days of observation, except for SOD activity where a decrease was seen on 3rd day. Qualitative profiling of phenolics showed that SA treatment enhanced the number of phenolic compounds as compared to control. It may be inferred that SA promotes resistance in mustard by enhancing the level of defense-related compounds and can be exploited to limit fungicidal use through induction of elevated levels of natural resistance.